Implementing ‘SKIPP’ for Enhancement of the Effectiveness the Discharge Planning at Hospital X: Implementasi SKIPP (Skala Indikator Pemulangan Pasien) untuk meningkatkan efektifitas Discharge Planning di Rumah Sakit X (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2024)
Planning for patient discharge is a complex process that aims to prepare the patient for the transition period in the hospital until the patient returns home safely. Long waiting times for patients to be discharged and less than optimal completeness of medical record files are problems at Perkebunan Jember Klinik Hospital. To overcome this problem, innovation was carried out by implementing the Patient Discharge Indicator Scale (SKIPP). The aim of this innovation program is to increase the effectiveness of comprehensive discharge planning. The methods used include observation, document review, interviews, focus group discussions, lectures and questions and answers. The results of the study showed a significant increase in nurses' knowledge from an average score of 53% to an average score of 90% after SKIPP socialization, the waiting time for patient discharge had met the established standards, with an average waiting time of only 1.7 hours and a review of six electronic medical records show that discharge planning, patient information and education have been completely documented in the electronic system. This shows that implementing SKIPP is an effective step in improving the quality of patient discharge services. The process includes assessing the patient's readiness the day before going home, giving a readiness score, submitting a discharge proposal to the doctor, and providing information and education to the patient and his family.